2021
DOI: 10.1021/acs.chemmater.1c01436
|View full text |Cite
|
Sign up to set email alerts
|

Conjugated Polyelectrolyte-Passivated Stable Perovskite Solar Cells for Efficiency Beyond 20%

Abstract: Developing large-scale perovskite solar cells requires highquality defect-free perovskite films with improved surface coverage. One of the most convenient ways to achieve this is through the incorporation of appropriate passivation molecules in the perovskite films. Herein, the effect of a novel conjugated polyelectrolyte, PHIA, is investigated for perovskite passivation by the comprehensive analysis of perovskite films and devices. The PHIA polymer significantly diminishes the trap states in perovskite films,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
41
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 41 publications
(43 citation statements)
references
References 34 publications
2
41
0
Order By: Relevance
“…Metallic lead is known to be the main nonradiative center and detrimental to the performance of the PSCs. Lots of reported conjugated molecules for PSCs anchor to the perovskite film via incorporation with uncoordinated Pb 2+ by amino groups, [ 46 , 49 , 53 , 69 ] carbonyl groups, [ 27 , 43 , 51 , 68 ] cyano groups, [ 51 ] sulfur atoms, [ 58 , 67 ] or fluorine atoms. [ 28 , 29 ] In PeLEDs, poly[(9,9‐bis(3’‐( N , N ‐dimethylamino)propyl)‐2,7‐fluorene)‐alt‐2,7‐(9,9‐dioctylfluorene)] (PFN), [ 73 ] PFN‐X (I, Br, Cl), [ 74 ] poly(9,9‐di‐n‐octylfluorenyl‐2,7‐diyl) (PFO), [ 75 ] poly(9,9‐bis(4′‐sulfonatobutyl)fluorene‐alt‐1,4‐phenylene) potassium (FPS‐K) and poly(9,9‐bis(4′‐sulfonatobutyl)fluorene‐alt‐1,4‐phenylene)tetramethylammonium (FPS‐TMA), [ 76 ] poly(fluorene‐ co ‐phenylene)‐based anionic conjugated polyelectrolytes, [ 77 ] and 1,3,5‐ tris (bromomethyl) benzene (TBB) [ 78 ] are reported to dramatically improve the device performance by defect passivation.…”
Section: Multifunctional π ‐Conjugated Additives F...mentioning
confidence: 99%
“…Metallic lead is known to be the main nonradiative center and detrimental to the performance of the PSCs. Lots of reported conjugated molecules for PSCs anchor to the perovskite film via incorporation with uncoordinated Pb 2+ by amino groups, [ 46 , 49 , 53 , 69 ] carbonyl groups, [ 27 , 43 , 51 , 68 ] cyano groups, [ 51 ] sulfur atoms, [ 58 , 67 ] or fluorine atoms. [ 28 , 29 ] In PeLEDs, poly[(9,9‐bis(3’‐( N , N ‐dimethylamino)propyl)‐2,7‐fluorene)‐alt‐2,7‐(9,9‐dioctylfluorene)] (PFN), [ 73 ] PFN‐X (I, Br, Cl), [ 74 ] poly(9,9‐di‐n‐octylfluorenyl‐2,7‐diyl) (PFO), [ 75 ] poly(9,9‐bis(4′‐sulfonatobutyl)fluorene‐alt‐1,4‐phenylene) potassium (FPS‐K) and poly(9,9‐bis(4′‐sulfonatobutyl)fluorene‐alt‐1,4‐phenylene)tetramethylammonium (FPS‐TMA), [ 76 ] poly(fluorene‐ co ‐phenylene)‐based anionic conjugated polyelectrolytes, [ 77 ] and 1,3,5‐ tris (bromomethyl) benzene (TBB) [ 78 ] are reported to dramatically improve the device performance by defect passivation.…”
Section: Multifunctional π ‐Conjugated Additives F...mentioning
confidence: 99%
“…The TPPpassivated perovskite films exhibit higher PL intensity when compared to the pristine perovskite film, demonstrating less non-radiative recombination in the passivated films. [39][40][41] The time-resolved photoluminescence (TRPL) measurements were conducted to study the effect of TPP passivation on perovskite film. It was observed that TRPL spectra also show a longer lifetime in the TPP-passivated perovskite film (τ = 82.1 ns) than that of the pristine (τ = 59.4) perovskite film, as displayed in Figure S2c.…”
Section: Resultsmentioning
confidence: 99%
“…The absorption of TPP‐passivated perovskite films shows a slight decrease relative to the pristine film, whereas all films exhibit a similar PL profile (emission peak at ≈763 nm), with only a minimum shift in peak position for the TPP‐passivated films, on excitation with 580 nm. The TPP‐passivated perovskite films exhibit higher PL intensity when compared to the pristine perovskite film, demonstrating less non‐radiative recombination in the passivated films [39–41] . The time‐resolved photoluminescence (TRPL) measurements were conducted to study the effect of TPP passivation on perovskite film.…”
Section: Resultsmentioning
confidence: 99%
“…The passivated device exhibited minimum charge collection at the interface, lower recombination and lesser traps, allowing for an improved charge transfer. As a result of the passivation, the device had a high PCE of 20.17% (0.50 mg mL −1 of PHIA) [ 156 ].…”
Section: Polymers In Perovskite Solar Cells (Pscs)mentioning
confidence: 99%